PENINGKATAN LITERASI ANAK MELALUI PENERAPAN STRATEGI PARENTING ‘MONTESSORI’ PADA ANAK BERUSIA 3-5 TAHUN: SASTRA ANAK - Rahmah, Muftihatur; Nensilianti, Nensilianti; Tuflih, Muhammad Alfian (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2024)
This research explores the application of Montessori parenting strategies to enhance literacy in children aged 3-5 years using Glenn Doman's approach. It focuses on implementing these strategies and the resulting improvements in children's literacy through fairy tales as a medium. Utilizing descriptive qualitative methods, data were collected via observation, interviews, notes, and documentation. The findings demonstrate an increase in literacy following the implementation of Montessori strategies. The fairy tale "Kancil and Harimau" by Dhani Larito serves as a suitable literacy medium, promoting visual literacy and stimulating children's sensory and motor skills.